Spectrophotometric determination of ammonia using ninhydrin assay and kinetic studies - Baker, Hutaf Mustafa; Alzboon, Khairieh Fadi (European Journal of Chemistry, 2015)
A spectrophotometric method for the determination of ammonia in aqueous media was investigated. This newly developed method for the reaction of ammonia with ninhydrin found to be simple, accurate and precise. A deep red color product was formed in the presence of sodium hydroxide at wavelength of 508 nm. The effects of variables such as temperature, time, acidity and reagents concentration have been evaluated to select the appropriate conditions for this reaction. Beer’s law is obeyed; the calibration curve is linear over the range of 2×10-4-1.4×10-3 M of ammonia with regression coefficient (r2) of 0.994 (n = 7). The calculated molar absorptivity and Sandell’s sensitivity values are 1.069×103 L/mol.cm and 0.015 μg/cm2, respectively. The limits of detection (LOD) and quantification (LOQ) are calculated to be 1.2×10-5 and 3.6×10-5 M, respectively. The intra-day accuracy expressed as relative error was less than 0.5% with precision (RSD) ranging from 0.49 to 1.55%. The inter-day accuracy ranged (RSD) from 0.49 to 1.90 % with a relative error was less than 1.50 %. The stoichiometry of this reaction was determined to be of 1:2 between ammonia and ninhydrin with first order reaction.